2018
DOI: 10.1021/acs.est.8b02625
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Dust and Dietary Exposure of Occupational Workers and Local Residents to Short- and Medium-Chain Chlorinated Paraffins in a Mega E-Waste Recycling Industrial Park in South China

Abstract: Four types of dust samples and nine categories of locally produced staple foods were collected from a mega e-waste recycling industrial park and its surrounding regions, and simultaneously analyzed for short-chain and medium-chain chlorinated paraffins (CPs) to estimate dust and dietary exposure and their combined effects on occupational workers and local residents. All samples related to e-waste activities contained considerably high concentrations of CPs. The highest dust concentration was found in e-waste w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 49 publications
3
50
1
Order By: Relevance
“… Limited occupational exposure data in LIMICs  Use of PPE sometimes optional and not always used (Ceballos et al, 2017;Julander et al, 2014 (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010), the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008  Non-carcinogenic risk determined by one study (Ohajinwa et al, 2019b) and considered low in all but one case involving dust.  Carcinogenic risk low in all cases reported in one study (Ohajinwa et al, 2019b (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010), the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008  Though concentrations have been determined in soils and dusts in surrounding ewaste dismantling areas (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010) the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008).  Non-carcinogenic risk calculated to be high in most cases (Ohajinwa et al, 2019b).…”
Section:  Results May Bementioning
confidence: 99%
See 2 more Smart Citations
“… Limited occupational exposure data in LIMICs  Use of PPE sometimes optional and not always used (Ceballos et al, 2017;Julander et al, 2014 (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010), the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008  Non-carcinogenic risk determined by one study (Ohajinwa et al, 2019b) and considered low in all but one case involving dust.  Carcinogenic risk low in all cases reported in one study (Ohajinwa et al, 2019b (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010), the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008  Though concentrations have been determined in soils and dusts in surrounding ewaste dismantling areas (Chen et al, 2018;Ohajinwa et al, 2019b;Wang et al, 2013), that are very high in some examples (Ma et al, 2009;Muenhor et al, 2010) the levels are low in comparison to indoor dusts in the UK, homes and offices and cars which residents are exposed to every day (Harrad et al, 2008).  Non-carcinogenic risk calculated to be high in most cases (Ohajinwa et al, 2019b).…”
Section:  Results May Bementioning
confidence: 99%
“…Chen et al (2018) measured concentrations of CPs in e-recycling workshop dust in China, finding concentrations of SCCPs and MCCPs ten times higher than in residential areas 2 km away and approximately 76 (SCCPs) and 80 (MCCPs) times higher than the reference homes 30 to 40 km away. All the concentrations of SCCPs were considerably higher than those observed by Wang et al (2013) whose highest measurement at the roadside in China was two orders of magnitude lower than the concentrations identified in reference homes by Chen et al (2018). The PBDE concentrations reported by Ohajinwa et al (2019a) were extremely low in comparison to all other authors other than the reference urban soil samples analysed by .…”
Section: Dust and Soilmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, the C 14 congeners dominated the profile, and Cl 8 CPs were the most abundant ones. Chen et al (2018) also reported the levels of MCCPs in the nine categories of locally produced staple foods collected from an e-waste recycling industrial park and its surrounding villages in China. As for SCCPs, when expressed on a fat weight basis, the highest MCCP levels were found in vegetables (local lettuce, 635,000 lg/kg fat, or 4,360 lg/kg ww) and fish (mrigal carp, 443,000 lg/kg fat), followed by shrimp, rice, duck, pork, shellfish, chicken and eggs.…”
Section: Mccpsmentioning
confidence: 99%
“…Wang et al (2019b) estimated the SCCP dietary intake from cereals and legumes to be 5,185 and 529 ng/kg bw per day, respectively, for an adult Chinese male. Chen et al (2018) estimated the dietary intake of SCCPs based on the analysis of several locally produced foods collected from an e-waste recycling industrial park and its surrounding villages in China. For adult local residents, the median dietary intake was estimated at 15,400 ng/kg bw per day, while in children it was 34,100 ng/kg bw per day.…”
Section: Sccpsmentioning
confidence: 99%